Effect of Adding Tuna Fish Bone Meal as a Source of Calcium Minerals in Feed in Freshwater Vannamei Shrimp (Litopenaeus vannamei) Cultivation - Umam, Khairul; Scabra, Andre Rachmat; Rahmadani, Thoy Batun Citra (Universitas Teuku Umar, 2024)
The aim of this research is to analyze the effect of giving tuna bone meal as a mineral source to vaname shrimp cultivated in freshwater media, at doses of 1%, 2%, 3% and 4%. Fish bones are a form of fish processing industry waste that contains the highest calcium among fish body parts, because the main components of fish bones are calcium, phosphorus and carbonate. The calcium content in tuna bone meal is higher than the calcium content in other fish bone meal, namely in catfish bone meal 13.48%, mandidihang fish bone meal 2.12%, catfish bone meal 30.95% and in fish bone meal tuna ranges from 23-39%. Based on research that has been carried out, the addition of tuna fish bone meal has a real influence on the growth of specific weight, absolute weight, specific length, absolute length but there is no significant difference to FCR. The best value was obtained in Treatment 5 with the addition of tuna bone meal at a dose of 4% ( 4 grams / 100gram feed). Specific weight values at P5 (2.85%), absolute weight (27.8), absolute length (6.00cm), specific length (3.46%)